Epidemiological study of endometriosis in the State of Maranhão (Research, Society and Development, 2022)
Objective: To carry out an epidemiological analysis of endometriosis in the State of Maranhão between 2017 and 2002. Methods: This is an exploratory, time series study of epidemiological data on endometriosis in the population of the State of Maranhão. Data were obtained through the SUS Information System (DATASUS). Results: It was verified that there were 2,113 hospitalizations for endometriosis in Maranhão between January 2017 and December 2021 and the most affected health region was São Luís. In addition, it was possible to observe that the most affected age group was from 40 to 49 years old, with 853 cases, followed by the population from 30 to 39 years old, with 601 hospitalizations. With regard to color, brown women were the most affected. There were two deaths, one in the health region of Açailândia and the other in the region of Rosário. The average hospital stay rate in the state was 2.8 days, the average hospitalization value was R$688.43 and the total amount spent on endometriosis in the analyzed period was R$1,460,154.35. Conclusion: It is possible to infer that endometriosis has a high incidence in Maranhão, especially in brown women, between 30 and 49 years old, with their hospitalizations more concentrated in the health regions of São Luís and Santa Inês. Although the disease is benign, it causes damage to the quality of life of patients in the physical and psychological scope, and it is important that health agencies create warning campaigns about the existence of the disease and what its symptoms are.